Climate Risk Management in Agricultural Extension System in Ethiopia - Lemma, Esayas; Denboba, Tolessa (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
The Ethiopian agricultural system is rain-fed, which makes it more vulnerable to climate variability and change. Climate change is expected to increase the frequencies of extreme climate events such as drought, flood, dry spell, heat, and cold waves, becoming more severe challenges in agricultural activities. Addressing these problems requires improving climate risk prediction capacity, designing preparedness mechanisms, and integrating weathers and climate information services into improved seeds, feeds, and fertilizer technologies. The Ministry of Agriculture (MoA) – with the support of the International Research Institute for Climate and Society (IRI) – initiated a project called Adapting Agriculture to Climate Today for Tomorrow (ACToday). This project collaborates with the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) East Africa to enhance climate risk under different management practices in agriculture sectors and strengthen the skill gaps. In this regard, MoA, in collaboration with International Livestock Research Institute (ILRI), IRI, National Meteorology Agency (NMA), and Ethiopian Institute for Agricultural Research (EIAR), conducted a 15-day long capacity building training on 'Climate Risk Management. The training included basic climate concepts, agro-meteorology advisory, agricultural extension services systems for federal agro-meteorology technical task force experts, and ATVET college instructors.